Of Receptors and Responses: Characterizing GPCR Signalling Pathways and Interactome Networks to Inform their Pharmacological Profiles - Zeghal, Manel (Université d'Ottawa | University of Ottawa, 2025)
G protein-coupled receptors (GPCRs) epitomize a preeminent class of drug targets, orchestrating a myriad of physiological processes. Notwithstanding their paramount biomedical importance, the advancement of GPCR-targeted drug discovery is impeded by the limitations of extant screening tools, which predominantly assess GPCR activation through agonist-induced G-protein and β-arrestin-2 activities. In this dissertation, we optimize and develop novel approaches to enhance the functional characterization of GPCRs and present non-canonical exemplars from the realm of GPCR-protein interactions. We introduce Tango-Trio, a robust high-throughput cell-based platform that enables the parallel profiling of both basal and agonist-dependent activities of GPCRs. This platform captures the functional diversity of GPCRs, including β-arrestin-1/2 couplings, selectivities, and receptor internalization signatures. By constructing cumate-induced basal activation curves for approximately 200 receptors, including over 50 orphans, Tango-Trio provides a valuable tool for comprehensive GPCR screening and characterization. Further, we develop the NbV5 tag system, an intracellular nanobody targeting the V5-tag, which enhances the study of protein-protein interactions (PPIs) in cellular assays. The smaller size of the V5-tag minimizes perturbations to protein stability and localization compared to larger functional moieties. This system is applicable in GPCR-based assays such as Bioluminescence Resonance Energy Transfer (BRET), NanoBiT, and Tango, and proves effective in live-cell imaging and microscopy, facilitating more accurate and versatile interrogation of GPCR signaling pathways. Finally, we investigate the dynamic isoform-specific interactions between GPCRs and 14-3-3 proteins, a family of adaptor proteins that regulate various cellular processes, including signal transduction, cellular stress responses, apoptosis, and cell cycle progression. Utilizing stable reporter cell lines expressing all seven human 14-3-3 isoforms, we perform high-throughput agonist-based screening across approximately 100 non-orphan GPCR. Notably, we identify the neurokinin 3 receptor (NK3) receptor as a key candidate for in-depth study and demonstrate that different combinations of 14-3-3 isoform dimers modulate NK3 receptor activity, including surface expression and signaling pathways, thereby highlighting the intricate regulatory mechanisms of GPCR function. Collectively, this work advances our understanding of GPCR signaling and PPIs in the proximal interactomes of GPCRs, offering new methodologies for drug discovery and providing insights into the sophisticated regulatory networks that underpin these receptors’ myriad functions.
Keywords: G protein-coupled receptors